ANALISIS GENDER MAHASISWA AKUNTANSI TERHADAP PEMAHAMAN MATA KULIAH PEMERIKSAAN AKUNTANSI - Ika Hari Mardiyani, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the significance of differences in accounting student understanding of the subjects accounting audits views of gender in Student Accounting Faculty of Economics University of Slamet Riyadi Surakarta Force Year 2012 – 2015. The research method used survey method, the type of data used quantitative and qualitative data, the data source used secondary data. Data collection methods used documentation. Data analysis techniques used normality test and test different. The results were obtained Z count equal to 0,493 -0,686 with probability value > 0,05 then Ho accepted means no significant difference to the students' understanding of accounting courses accounting audits views of gender in Student Accounting Faculty of Economics University of Slamet Riyadi Surakarta Force Year 2012 – 2015, So the hypothesis which states that: